2013
DOI: 10.1121/1.4773257
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approximations for low frequency band gaps in periodic arrays of elastic shells

Abstract: This paper presents and compares three analytical methods for calculating low frequency band gap boundaries in doubly periodic arrays of resonating thin elastic shells. It is shown that both Foldy-type equations (derived with lattice sum expansions in the vicinity of its poles) and a self-consistent scheme could be used to predict boundaries of low-frequency (below the first Bragg band gap) band gaps due to axisymmetric (n=0) and dipolar (n=1) shell resonances. The accuracy of the former method is limited to l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The detailed description of the model can be found in a previous work, 8 so here it is only briefly outlined. Consider an effective medium as a replacement of a doubly periodic array of elastic shells in air.…”
Section: Self-consistent Model For Effective Properties Of Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description of the model can be found in a previous work, 8 so here it is only briefly outlined. Consider an effective medium as a replacement of a doubly periodic array of elastic shells in air.…”
Section: Self-consistent Model For Effective Properties Of Arraymentioning
confidence: 99%
“…Analytical approximations for low frequency bandgap boundaries in the arrays of elastic shells are presented in Ref. 8. It is shown that as a result of the variation in bandgap width with filling fraction of scatterers in the array, the low transmission bands are wider in denser arrays.…”
Section: Introductionmentioning
confidence: 99%
“…4, use Fourier expansions for the wave field and periodic material properties to compute the dispersion behavior, yet can experience convergence issues for highly contrasting material properties. 9 Chen and Ye 3 and Krynkin et al 10 considered spherical harmonics via separation of variables to compute the dispersion relationship for given fluid, and respectively, fluid-solid crystals. Alternatively, transfer matrices 7 are well-suited for one-dimensional systems whereas finite difference techniques can also be used to numerically compute the dispersion of complex or finite periodic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Other Helmholtz equation studies of this type include work on two-dimensional arrays of thick-walled split-ring resonators [16] and two-dimensional arrays of closely packed solid cylinders [17]. Estimates for the upper and lower bounds of the first band gap in elastic resonator array problems have also been considered [18]. Research on resonator arrays has also been conducted extensively for Maxwell's equations, including a numerical study on determining effective optical constants of a two-dimensional array of infinitesimally thin split-ring resonators [19].…”
Section: Introductionmentioning
confidence: 99%